EFEKTIFITAS SISTEM PAKAR UNTUK MENDIAGNOSA ANEMIA TERHADAP KETEPATAN KEJADIAN ANEMIA PADA REMAJA SANTRI - Wahida Yuliana; Iis Hanifah; Tutik Hidayati (Rena Cipta Mandiri, 2025)
An expert system is a computer program designed to make decisions similar to those made by one or more experts. An expert system is the use of technology that can simplify a person's work. Based on data, nutritional anemia in adolescents in Probolinggo Regency is 9.3%. The purpose of this study is to analyze the effectiveness of an expert system for diagnosing anemia on the accuracy of anemia incidents in adolescent students. The research design is quasi-experimental. The population in this study were all adolescent students who were final year students at the Hafshawaty Islamic Boarding School and were in the process of college, totaling 60 adolescents. The sampling technique used is total sampling. The steps will be done by dividing control and intervention groups at the same time. The analysis used is the chi-square statistical test with a significance level of 95% (alpha 0.05) using SPSS. The results of the study are the use of expert systems with the highest accuracy of anemia diagnosis is Correct and Using expert systems as many as 30 people (50.0%). The category does not use expert systems and inaccurate diagnoses as many as 25 people (41.7%). The results of the statistical test obtained showed a p-value of 0.000 <0.05 meaning there is an Effectiveness of Expert Systems to diagnose anemia on the Accuracy of Anemia Incidents in Adolescent Students at Pondok Putri Hafshawaty. It is hoped that expert systems can be used as technology to perform early detection independently in cases of anemia. The output of this study will be published through the Accredited National Journal Sinta.